The Sesame Street library, v. 3 - Frith, Michael (New York : Funk and Wagnalls, 1978)
With Jim Henson's Muppets.
Contents: Featuring the letters E and F and the number 3.
Keywords: Alphabet; Number Concept; Counting; Reading